INVESTIGATING THE ROLE OF TOTAL QUALITY MANAGEMENT, ENTREPRENEURIAL ORIENTATION, AND ORGANIZATIONAL EXCELLENCE IN DETERMINING THE ORGANIZATIONAL PERFORMANCE IN DUBAI POLICE - Saleh Almazrouei; Norziani Dahalan (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The purpose of this study is to examine the role of total quality management, entrepreneurial orientation, organizational excellence towards organizational performance from the context of Dubai Police. A sample of 453 valid responses through online survey questionnaire was collected and analzyed. More specifically, descriptive statistics, correlational and demographic analyses and both measurement model and structural model was assessed. The study findings through measurement model confirm the reliability, validity, internal consistency, and discriminant validity of the latent constructs. Finally, the findings through PLS-SEM approach confirms that direct and significant relationship between total quality management, entrepreneurial orientation, organizational excellence, and organizational performance, respectively. Besides, some useful policy implications and study limitations are also discussed to determine the future directions of the upcoming studies.